A importância dos jogos na disciplina de geografia - Alves, Alessandra (2018)
This work presents the report of an experience on the use of play activities in Geography teaching with the students of the 7th grade of the Adélia Rossi Arnaldi State College in Paranavaí-PR, aiming to highlight the importance of working in classroom with other educational didactic resources in teaching learning, in order to arouse interest and facilitate student learning. For the accomplishment of this research was used the technique of the qualitative research, of the type study of case. The playful can be used as a way to bring about a more pleasant and meaningful learning, stimulating the knowledge, and thus, the development of the child. During the application of the games, being a memory game of States and capitals and puzzle of Brazilian maps, there were errors and correctness, but the student can reverse this result, doing again, where they had to practice the logical reasoning for the development of this activity.